Adjunctive use of prednisolone in the treatment of free-flowing tuberculous pleural effusion: A retrospective cohort study. (June 2018) - Sun, Fenfen; Li, Li; Liao, Xiuqing; Yan, Xiaofeng; Han, Rui; Lei, Wenhui; Cao, Hui; Feng, Mingxia; Cao, Guoqiang
Abstract: Background: Adjunctive use of corticosteroids with anti-tuberculosis (TB) therapy has been reported to benefit people with tuberculous pleural effusion (TPE), while there is a paucity of data to support it as routine use. TPE can be subdivided into free-flowing type and loculated type. We evaluated the effects of adjunctive prednisolone therapy on functional sequelae, pleural thickening and pleural adhesions in patients with free-flowing TPE. Methods: This is a retrospective cohort study, conducted from Jan 2013 to Dec 2016 (ChiCTR-ORC-16009267). All the patients were diagnosed with TPE, and treated with standard 4-drug anti-TB chemotherapy regimen and complete drainage of the effusion. We compared the incidence of a composite of roentgenographic sequelae (pleural thickening of > 2 mm, or pleural adhesions and costophrenic angle > 90°), or restrictive functional sequelae (FVC/FVC pre or TLC/TLC pre < 80%) between those who received adjunctive prednisolone therapy and those who did not. Results: The final cohorts consisted of 135 subjects. Of those, 56 received adjunctive prednisolone therapy and 79 did not. The incidence of a composite of roentgenographic sequelae or restrictive functional sequelae was significantly decreased in the prednisolone group as compared with the control group (51.8% vs. 75.9%; RR 2.83, 95% confidence interval, 1.27–6.31, P = 0.011). No serious side effects due to corticosteroid were noted. Conclusions: This study detected a significant association between adjunctive prednisolone therapy and decreased incidence of a composite of radiographic sequelae, or functional sequelae in HIV-negative, free-flowing type TPE patients treated with adjunctive prednisolone. Highlights: A retrospective cohort study. Adjunctive use of corticosteroid may benefit free-flowing TPE patients. Reduced incidence of roentgenographic sequelae or restrictive functional sequelae.